Herpes simplex encephalitis in adults: A case highlighting the diagnostic superiority of MRI - Gurung, Kismat; Shrestha, Rejina (Journal of Gandaki Medical College-Nepal, 2025)
Herpes simplex encephalitis (HSE) is a rare but severe neurological condition caused by the herpes simplex virus, primarily affecting the temporal lobes and limbic system. This case report presents a 78-year-old Asian man who was admitted to the emergency department with a two-day history of fever and one day of altered consciousness. His past medical history was significant for aortic valve replacement surgery, with no other notable comorbidities. Initial clinical examination and laboratory investigations, including CT and cerebrospinal fluid analysis, were unremarkable. However, MRI of the brain revealed characteristic findings consistent with HSE, including areas of altered signal intensity in the left temporal lobe, hippocampus, insular cortex, and right thalamus. The patient was diagnosed with herpes simplex encephalitis, confirmed by MRI findings. This case underscores the importance of early neuroimaging, particularly MRI, in diagnosing HSE, which remains a clinical challenge due to its non-specific initial presentation. Prompt initiation of antiviral therapy, such as intravenous acyclovir, is critical in reducing morbidity and mortality associated with this condition.